Effect of Dietetic Obesity on Testicular Transcriptome in Cynomolgus Monkeys - Zhang, Yanru; Qi, Jia; Zhao, Juan; Li, Miaojing; Zhang, Yulin; Hu, Huizhong; Wei, Liangliang; Zhou, Kai; Qin, Hongyu; Qu, Pengxiang; Cao, Wenbin; Liu, Enqi (Genes, 2023)
Obesity is a metabolic disorder resulting from behavioral, environmental and heritable causes, and can have a negative impact on male reproduction. There have been few experiments in mice, rats, and rabbits on the effects of obesity on reproduction, which has inhibited the development of better treatments for male subfertility caused by obesity. Nonhuman primates are most similar to human beings in anatomy, physiology, metabolism, and biochemistry and are appropriate subjects for obesity studies. In this investigation, we conducted a transcriptome analysis of the testes of cynomolgus monkeys on high-fat, high-fructose, and cholesterol-rich diets to determine the effect of obesity on gene expression in testes. The results showed that the testes of obese monkeys had abnormal morphology, and their testes transcriptome was significantly different from that of non-obese animals. We identified 507 differentially abundant genes (adjusted p value < 0.01, log2 [FC] > 2) including 163 up-regulated and 344 down-regulated genes. Among the differentially abundant genes were ten regulatory genes, including IRF1, IRF6, HERC5, HERC6, IFIH1, IFIT2, IFIT5, IFI35, RSAD2, and UBQLNL. Gene ontology (GO) and KEGG pathway analysis was conducted, and we found that processes and pathways associated with the blood testes barrier (BTB), immunity, inflammation, and DNA methylation in gametes were preferentially enriched. We also found abnormal expression of genes related to infertility (TDRD5, CLCN2, MORC1, RFX8, SOHLH1, IL2RB, MCIDAS, ZPBP, NFIA, PTPN11, TSC22D3, MAPK6, PLCB1, DCUN1D1, LPIN1, and GATM) and down-regulation of testosterone in monkeys with dietetic obesity. This work not only provides an important reference for research and treatment on male infertility caused by obesity, but also valuable insights into the effects of diet on gene expression in testes.